Cognitive Expertise: An ALE Meta‐Analysis. Issue 1 (14th October 2015) - Neumann, Nicola; Lotze, Martin; Eickhoff, Simon B.
Abstract: Expert performance constitutes the endpoint of skill acquisition and is accompanied by widespread neuroplastic changes. To reveal common mechanisms of reorganization associated with long‐term expertise in a cognitive domain (mental calculation, chess, language, memory, music without motor involvement), we used activation likelihood estimation meta‐analysis and compared brain activation of experts to nonexperts. Twenty‐six studies matched inclusion criteria, most of which reported an increase and not a decrease of activation foci in experts. Increased activation occurred in the left rolandic operculum (OP 4) and left primary auditory cortex and in bilateral premotor cortex in studies that used auditory stimulation. In studies with visual stimulation, experts showed enhanced activation in the right inferior parietal cortex (area PGp) and the right lingual gyrus. Experts' brain activation patterns seem to be characterized by enhanced or additional activity in domain‐specific primary, association, and motor structures, confirming that learning is localized and very specialized. Hum Brain Mapp 37:262–272, 2016 . ©2015 Wiley Periodicals, Inc.